Delphi 3SuperBible - Paul B Thurrott...[et al.] (Waite Group Press, 1997)
The book presents software Delphi 3 SuperBible. It discuses about Delphi3's classes, properties, methods, events, statements, procedures, and functions. The CD-ROM in the back of this book contains all the source code and extended examples, as well as a trial version of WebHub, the powerful Delphi Web-server utility